Withdrawal: Quantitative Synthesis of Temperature‐responsive Polymersomes by Multiblock Polymerization. Issue 29 (5th July 2021) - Liu, Xiaoling; Zhou, Dongxu; Feng, Yunbo; Gou, Jing; Li, Chenxi; He, Chao; Zhao, Weifeng; Sun, Shudong; Zhao, Changsheng; Appelhans, Dietmar; Voit, Brigitte
Abstract : This Communication, published online on 14 August 2019 in Wiley Online Library (onlinelibrary.wiley.com), has been withdrawn by agreement between the corresponding authors, the journal's Executive Committee, and Wiley‐VCH GmbH, Weinheim. The withdrawal has been agreed upon following the explanation by the authors that problems with a microscopy image presented in Figure 4 of the article cannot be fully clarified.